Paternal Hemizygosity in 11p15 in Mole-like Conceptuses: Two Case Reports. Issue 44 (November 2015) - Sunde, Lone; Lund, Helle; J Sebire, Neil; Grove, Anni; Fisher, Rosemary A.; Niemann, Isa; Kjeldsen, Eigil; Andreasen, Lotte; Hansen, Estrid Staehr; Bojesen, Anders; Bolund, Lars; Nyegaard, Mette
Abstract : Abstract: Hydatidiform mole is an abnormal human pregnancy characterized by the fetus being absent or nonviable, and the chorionic villi being vesicular and with trophoblastic hyperplasia. Most often, the mole phenotype is seen in conceptuses with an excess of paternally inherited genome set(s) relative to maternally inherited genome set(s), suggesting that the phenotype is caused by an excess of genome with a paternal imprinting pattern. However, it is unknown if correct parental origin of every imprinted gene is crucial for normal early differentiation or if abnormal parental imprinting of only one, or some, gene(s) can cause the mole phenotype. Two conceptuses included in the Danish Mole Project stood out since they presented with vesicular chorionic villi and without signs of fetal differentiation, and had apparently biparental diploid genomes, and no mutations in NLRP7 or KHDC3L were detected in the mothers. These conceptuses were subjected to a centralized histopathological revision and their genetic complements were scrutinized using fluorescence in situ hybridization, and DNA-marker and array comparative genomic hybridization analyses. Both conceptuses showed dysmorphic chorionic villi with some similarities to hydatidiform moles; however, no definite florid trophoblast hyperplasia was observed. Both conceptuses showed paternal hemizygosity of 11pter-11p15.4, most likely in nonmosaic state. Our findings suggest that the product of one (or a few) maternally expressed gene(s) on the tip of chromosome 11 is necessary for normal early embryonic differentiation. However, since the present two cases did not exhibit all features of hydatidiform moles, it is likely that abnormal parental imprinting of genes in other regions contribute to the phenotype of a hydatidiform mole.